New frog (Brachycephalidae: Eleutherodactylus) from the Western Flank of the Cordillera Oriental of Colombia - Arroyo, Sandy B. (Zootaxa, 2007)
A new Eleutherodactylus species is described from the western flanks of the Cordillera Oriental in the Departamento de Santander. It is a member of the Eleutherodactylus conspicillatus phenetic group. It appears to be most closely relate to E. carranguerorum.